Organizational Trust Level in Hospitals Through Nurses' Evaluation - Elif Baş; Havva Öztürk (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: This descriptive and cross-sectional study was conducted to determine the level of organizational trust in hospitals and the factors that affect it through the opinions of nurses. Method: The research population consisted of all nurses working in a university, private and public hospitals in Trabzon city center (N = 1881). The sample consisted of 319 nurses selected from these hospitals utilising stratified sampling. The data were collected using the information form and the "Organizational Trust Scale" and analyzed using percentage, Kruskall Wallis and Mann Whitney-U tests. Results: In the study, the average score on the Organizational Trust Scale of nurses, 81.2% of whom were women, 62.4% of whom had undergraduate or postgraduate degrees, 58% of whom worked in public hospitals and 40.1% of whom had less than 5 years of professional experience, was determined as follows: 4.08 (SD=0.66), subscale mean scores are 4.28 (SD=0.84) for trust in the manager, 3.33 (SD=1.12) for trust in the institution and 4.46 (SD=0.76) for trust in colleagues were found. Statistically significant differences were detected between the hospital where nurses worked, their feeling of safety, their intention to leave the institution and their dissatisfaction with the institution, and the total score of the organizational trust scale (p <0.05). Conclusion: Overall, nurses' organizational trust in their hospitals is at a medium level. Nurse manager and nurses with low years of experience and those working in internal medicine clinics have more trust in their hospitals. In addition, nurses in public hospitals trust their colleagues more, nurses in university hospitals trust their hospital and managers more.